2020
DOI: 10.1111/1556-4029.14519
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Pathological Considerations of a Unique Case of “Complicated Suicide”*,†

Abstract: In the forensic literature, peculiar and uncommon cases of suicides defined as "complicated" are reported. In these circumstances, the suicide method chosen by the victim fails, and death occurs due to a subsequent unforeseen accidental event defined as secondary trauma. Through retrospective examination of 25,512 autopsies in 27 years (1993-2019) at the Bureau of Legal Medicine of Milan, a unique case of complicated suicide was identified from a total of 4497 suicides. It concerns an elderly man who, after ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The most common result from an accidental fatal fall during attempted hanging. 3,5,6 Russo et al reported a case where the victim was decapitated while trying to hang himself. 7 Dickerson et al report a case where a 36-year-old man tried to overdose in a chemical toilet but the dangerous chemical substances, extreme heat, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common result from an accidental fatal fall during attempted hanging. 3,5,6 Russo et al reported a case where the victim was decapitated while trying to hang himself. 7 Dickerson et al report a case where a 36-year-old man tried to overdose in a chemical toilet but the dangerous chemical substances, extreme heat, etc.…”
Section: Discussionmentioning
confidence: 99%
“…They are rare. [3][4][5] We present the case of a 60-year-old man whose body was found in his house, extensively burnt and with thoracic and abdominal traumas from glass fragments. After excluding homicide, the sequence of events was reconstructed revealing a complicated suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal waterboarding is therefore definable as a primary and planned complex suicide [ 22 , 23 ] since two different independent and lethal methods are applied simultaneously [ 24 ]. On one hand, the soaked canvas bag provokes a direct physical obstruction of the mouth and the nostrils which is augmented by the respiratory activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the forensic literature, complex suicides refer to highly uncommon suicides in which multiple detrimental methods are used simultaneously or in chronological succession to avoid possible ineffectiveness of one of the chosen methods and achieving a guaranteed fatal outcome [ 39 , 40 , 41 ]. On the other hand, the term “complicated suicide” refers to a suicide in which the method established by the victim fails, but death still occurs due to an accidental secondary trauma that was not planned [ 42 , 43 ]. As for complex and complicated suicides, the distinction between violent and non-violent suicides is based on the first detrimental modality that was chosen and applied.…”
Section: Methodsmentioning
confidence: 99%